Reversible ubiquitination regulates the Smad/TGF-β signalling pathway. (25th October 2006) - Wicks, S.J.; Grocott, T.; Haros, K.; Maillard, M.; Dijke, P. ten; Chantry, A.
Abstract : TGF-β (transforming growth factor-β) signals through serine/threonine kinase receptors and intracellular Smad transcription factors. An important regulatory step involves specific ubiquitination by Smurfs (Smad–ubiquitin regulatory factors), members of the HECT (homologous to E6-associated protein C-terminus) ubiquitin ligase family, which mediate the proteasomal degradation of Smads and/or receptors. Recently, we have defined a novel interaction between Smads and UCH37 (ubiquitin C-terminal hydrolase 37), a DUB (de-ubiquitinating enzyme) that could potentially counteract Smurf-mediated ubiquitination. We have demonstrated specific interactions between UCH37 and inhibitory Smad7, as well as weaker associations with Smad2 and Smad3. Importantly, Smad7 can act as an adaptor able to recruit UCH37 to the type I TGF-β receptor. Consequently, UCH37 dramatically up-regulates TGF-β-dependent gene expression by de-ubiquitinating and stabilizing the type I TGF-β receptor. Our findings suggest that competing effects of ubiquitin ligases and DUBs in complex with Smad7 can serve to fine-tune responses to TGF-βs under various physiological and pathological conditions. Studies are currently under way using activity-based HA (haemagglutinin)-tagged ubiquitin probes to identify the full spectrum of DUBs that impact on Smad/TGF-β signalling activity.